The Relationship between Generation Gap and Social Harms among Teenagers in Tehran - Zeynab Meynaghi aghdam; Khalil Mirzaei; Khadije Safiri; Aliye Shekarbeigi (فصلنامه رفاه اجتماعی, 2022)
Introduction: The phenomenon of generation gap between parents and children, as yesterday's generation and today's generation in recent decades, has become one of the most important issues in the field of family pathology. The aim of this study was to study the relationship between generation gap and social damages among adolescents in Tehran. Method: This research is descriptive-analytical and quantitative in terms of methodology and survey type, considering cross-sectional time criterion. The statistical population consisted of families with 10-19 years old children in Tehran who were selected by multi-stage cluster sampling in the nine-month period in proportion to the families living in districts 2, 9, and 16 using Cochran formula. The instrument was a researcher-made questionnaire, and to determine its validity, face validity method was used to calculate the validity of Cronbach's alpha method, and SPSS and Lisrel software were used to analyze the data. Findings: The results of the research indicated that generation gap has a significant and direct relationship with the incidence of social damages among adolescents in Tehran. Also, generation gap has a significant and direct relationship with aggression, theft, dropout, suicide, drug use and running away from home. Discussion: Social issues are the product of the disrupted process of socialism and its reproduction in families and society, the lack of management of the gap between generations on the one hand is an alarm for the collapse of the family system, which has a special place in the Islamic religion and Iranian culture, and on the other hand, this gap along with the occurrence of social damages will be one of the main obstacles on the way of the social development of the country.